Efektifitas Pembelajaran Al-Quran Dengan Metode Tilawati Di TPA Ali Hikmah Sangatta - Anisa Dian Andini; Faelasup Faelasup (AL-AMIYAH: Jurnal Ilmiah Multidisiplin, 2024)
This research aims to analyze the effectiveness of Al-Quran learning using the tilawati method at the Ali Hikmah Sangatta Al-Quran Education Park (TPA). The research method used is a descriptive qualitative approach. The subjects of this research were teachers and students at TPA Ali Hikmah Sangatta. The research results showed that the tilawati method was applied consistently at TPA Ali Hikmah Sangatta and improved students' Al-Quran reading skills. Most of the students showed a significant increase in their recitation skills with correct recitation and appreciation of the meaning of the verses of the Koran. Students respond positively to this method, feel more confident, and are motivated to study the Koran further. However, this research also found several challenges in implementing the tilawati method, such as limited learning time, variations in student abilities, and the availability of adequate learning media. To overcome this challenge, it is recommended that learning facilities be improved, teachers are continuously trained, an individualist approach is implemented, time arrangements are more flexible, and a more integrative curriculum is developed. This research concludes that the tilawati method is an effective approach to learning Al-Quran at TPA Ali Hikmah Sangatta and makes an important contribution to developing Al-Quran learning strategies that can be applied in various other Islamic educational institutions